How tastes change - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Deprived of their staple cereal teff (Eragrostis tef), the ten thousand Ethiopian refugees in Kenya have started to use rice as a substitute for making their beloved flat bread, injera, which is used as a scoop for eating stews. Teff-based injera is...